Circulating microRNAs in Response to Exercise Training in Healthy Adults - Zhou, Qiulian; Shi, Chao; Lv, Yicheng; Zhao, Chenglin; Jiao, Zheng; Wang, Tianhui (Frontiers in Genetics, 2020)
Circulating microRNAs (miRNAs, miRs) have great potential as cardiac biomarkers and they are also being explored for their roles in intercellular communication and gene expression regulation. The analysis of circulating miRNAs in response to exercise would provide a deeper understanding of the molecular response to physical activity and valuable information for clinical practice. Here, eight college students with an average age of 20.75 were recruited to participate in cardiopulmonary exercise testing and 1 hour acute exercise training. Blood samples were collected and serum miRNAs involved in angiogenesis, inflammation and enriched in muscle and/or cardiac tissures were analyzed before and after cardiopulmonary exercise and acute exercise. The miRNAs we detected were miR-1, miR-20a, miR-21, miR-126, miR-133a, miR-133b, miR-146, miR155, miR-208a, miR-208b, miR-210, miR-221, miR-222, miR-328, miR-378, miR-499, and miR-940. We found that serum miR-20a was decreased significantly after cardiopulmonary exercise testing and serum miR-21 was increased after acute exercise training. In addition, no robust correlation was identified between the changes of these miRNAs and makers of cardiac function and exercise capacity. Future studies are highly needed to define the potential use of these circulating miRNAs as useful biomarkers of exercise training, and disclose the biological function of circulating miRNAs as physiological mediators of exercise-induced cardiovascular adaptation.